Impact of thermal treatment on the quality, total antioxidant and antibacterial properties of fermented camel milk - Nagwa Hussein Ismail Abou-Soliman; Hagar Saeed Abd-Rabou; Sameh Awad; Amel A. Ibrahim (Scientific Reports)
Abstract This study investigated the impact of thermal treatments on the quality, antioxidant, and antibacterial properties of fermented camel milk during refrigerated storage. Two thermal treatment categories were applied: moderate (63 °C for 30 min and 72 °C for 15 s) and high (85 and 90 °C for 15 s and 30 min). Findings indicated that raw camel milk was found to be microbiologically unacceptable. Heating milk to 90 °C for 30 min notably reduced fermentation time, increased fermented milk viscosity, and altered whey protein electrophoretic patterns. While thermal treatments below 90 °C boosted lactic acid bacteria count in fermented milk compared to raw milk-derived samples (control), all treatments exceeded the recommended standards throughout storage. Thermal treatment decreased the proteolysis degree and DPPH radical scavenging activity but enhanced the ferric-reducing power of fermented milk compared to the control. Among, thermal treatments, samples from milk heated at 90 °C exhibited the highest scavenging activity and reducing power. Antibacterial efficacy against Salmonella Typhimurium surpassed that against Escherichia coli and Staphylococcus aureus; the most pronounced effect was observed in samples from milk heated at 90 °C. In conclusion, thermal treatment of camel milk is crucial to ensure sufficient hygiene for safe milk consumption. Heating camel milk at 90 °C before fermentation positively impacted most of the studied properties.